“Because Work Time Is Life Time” – Employees’ Perceptions of Individual Overemployment, Its Causes and Its Consequences - Hiemer, Julia; Andresen, Maike (Frontiers in Psychology, 2019)
Many employees would prefer to reduce work time i.e. they are overemployed. However, the concept of overemployment is poorly understood. The purpose of this article is to define overemployment from employees’ point of view, to explain why people work more than they prefer and to understand the individual consequences thereof. We investigate twenty-six overemployed employees using a Grounded Theory approach. We find that overemployment is a four-dimensional experience consisting of work time length, work time competition (with time outside work), work time distribution on tasks and work density. A self-reinforcing circle of personal and situational drivers explains the persistence of overemployment. Regarding the psychosocial consequences of overemployment, our findings show large variations, whereby work time sovereignty seems to play a moderating role. This study provides a multidimensional framework of overemployment that provides a basis for understanding employees’ perceptions and behaviour regarding overemployment and for deriving appropriate actions to reduce overemployment.